A review of high performance work practices (HPWPs) literature and recommendations for future research in the hospitality industry. Issue 1 (8th January 2018) - Murphy, Kevin; Torres, Edwin; Ingram, William; Hutchinson, Joe
Abstract : Purpose: The present research aims to examine the scholarly literature on high-performance work practices (HPWPs). Relevant comparisons were made between the hospitality industry, service industry and various other contextual environments in general business that might impact the choice and implementation of HPWPs, and a set of work practices was proposed for the hospitality industry. Design/methodology/approach: A comprehensive review was conducted of scholarly literature related to HPWPs that was published in the past 25 years (1991-2015). A total of 89 scholarly articles were considered in this summary. Based on this review, HPWPs in the hospitality industry were compared and contrasted with other industry sectors. Findings: There is little consensus among researchers concerning specific HPWPs that should be used by every company to improve their organizational- or individual-level performance. Thus, a specific set of 13 HPWPs that take into consideration the unique characteristics of the industry, based on a review of empirical research, was identified for the hospitality industry as a starting point for future research in the hospitality industry. Originality/value: Following a comparison of HPWPs in the hospitality, services literature and manufacturing-based industry context, the authors extend the body of knowledge and propose a set of HPWPs for future research in the hospitality industry. HPWPs can have positive impacts on both organizational- and individual-level performance. Thirteen specific hospitality HPWPs were identified that are most beneficial, and the circumstances under which they might yield optimal results enhance the scholar's understanding of HPWPs and provide guidance to human resource professionals to make evidence-based decisions. A better understanding of HPWPs can assist human resource professionals in making policy decisions that optimize the use of human capital in their organizations.